The Influence of Transjudicial Conversation in the Cross-fertilization of Philippine Human Rights Jurisprudence - James Gregory Alcaraz Villasis; Naparat Kranrattanasuit (Sriwijaya Law Review, 2024)
Transjudicial conversation refers to the domestic court's judicial practice of cross-citing foreign decisions on common and shared human rights issues. Scholars have argued that this phenomenon facilitates the cross-fertilisation of rights norms and standards across territories. While this has been documented and studied in various jurisdictions, its incidence and effect in the Philippine context is yet to be fully understood. The paper thus seeks to explore the extent of such influence in the Philippine setting, specifically in the development of domestic human rights jurisprudence. In order to examine its impact, this research employs a qualitative research design. Select cases on free speech and religious exercise rights were analysed using doctrinal and content analysis approaches. These cases were purposively chosen, considering that Philippine provisions on these rights have shown close affinity with foreign constitutions. The analysis reveals that the participation of the Philippine Supreme Court in the transjudicial conversation phenomenon generally causes the cross-border fertilisation of human rights norms. Particularly, the impact of this engagement contributes to filling the gap in the domestic understanding of human rights concepts, expanding existing legal systems such as human rights and penal laws, and aligning national human rights systems with international laws. Such impacts enrich the domestic understanding of free speech and religious rights, specifically drawing bright lines between legitimate state intervention and individual enjoyment of the rights.